Combination of Intravenous Umbilical Cord-Derived Mesenchymal Stem Cell Therapy and Pulmonary-Targeted Inhalation of an Insulin-Stem Cell Mixture for Type 2 Diabetes Mellitus: Under the Vinski Protocol - Deby Susanti Pada Vinski; Andi Ibnu Hajar; Natasha Cinta Vinski (Journal of World Science, 2026)
Type 2 diabetes mellitus (T2DM) remains a global metabolic disorder characterized by progressive insulin resistance, impaired pancreatic beta-cell function, chronic inflammation, and increased risk of systemic complications. Current therapeutic approaches primarily focus on glycemic control; however, they do not fully address the underlying regenerative and inflammatory aspects of the disease. This study aimed to evaluate the feasibility, preliminary clinical outcomes, and safety of a combination intervention consisting of intravenous umbilical cord-derived mesenchymal stem cell (UC-MSC) therapy and pulmonary-targeted inhalation of an insulin-stem cell mixture under the Vinski Protocol. A retrospective pilot clinical study was conducted using medical record data from 10 patients with T2DM treated at Celltech Stem Cell Centre, Jakarta, Indonesia. Clinical evaluations included changes in HbA1c, fasting blood glucose, fasting C-peptide, medication or insulin requirements, pulmonary observations, and safety outcomes. The findings indicated that the combination approach was clinically feasible and generally well tolerated, with preliminary observations suggesting potential improvements in metabolic parameters and patient clinical status. However, interpretation of outcomes remains limited due to the small sample size, retrospective design, absence of a control group, and potential influence of concurrent diabetes management. The integration of systemic UC-MSC therapy with pulmonary-targeted adjunctive treatment represents an innovative precision regenerative strategy for T2DM management. Further prospective controlled clinical trials with larger populations are required to validate efficacy, determine optimal protocols, and establish long-term safety.